Protein Kinase Activity of Phytochrome A Positively Correlates With Photoresponses in Arabidopsis - Hoang, Quyen T. N.; Cho, Jae-Yong; Choi, Da-Min; Shin, Ah-Young; Kim, Jin A.; Han, Yun-Jeong; Kim, Jeong-Il (Frontiers in Plant Science, 2021)
Plant phytochromes are known as autophosphorylating serine/threonine protein kinases. However, the functional importance of their kinase activity is not fully elucidated. Previously, the kinase activity is shown to be necessary for the function of Avena sativa phytochrome A (AsphyA) using transgenic plants with mutants displaying reduced kinase activity, such as K411L and T418D. In this study, we isolated and analyzed two AsphyA mutants, K411R and T418V, that showed increased kinase activity. Transgenic phyA-201 plants with these mutants showed hypersensitive responses to far-red (FR) light, such as shorter hypocotyls and more expanded cotyledons than those of control plant (i.e., transgenic phyA-201 plant with wild-type AsphyA). Contrary to the mutants with reduced kinase activity, these mutants accelerated FR-induced phosphorylation and subsequent degradation of phytochrome-interacting factor 3 (PIF3) in Arabidopsis. Moreover, elongated hypocotyl 5 (HY5), a critical positive regulator of photoresponses in plants, accumulated in higher amounts in the transgenic plants under FR light than in the control plant. In addition, PIF1 degradation was accelerated in the transgenic plants. Consequently, the transgenic plants exhibit higher germination frequencies than the control plant. Collectively, our results demonstrate that the AsphyA mutants with increased kinase activity are hyperactive in plants, supporting a positive relationship between the kinase activity of phytochromes and photoresponses in plants.